F-Type ATP Synthase Assembly Factors Atp11 and Atp12 in Arabidopsis - Duan, Zhikun; Li, Kaiwen; Zhang, Lin; Che, Liping; Lu, Lizhen; Rochaix, Jean-David; Lu, Congming; Peng, Lianwei (Frontiers in Plant Science, 2020)
Atp11p and Atp12p are members of two chaperone families essential for assembly of the mitochondrial ATP synthase in Saccharomyces cerevisiae and Homo sapiens. However, the role of their homologs in higher plants is unclear with regard to the assembly of both chloroplast ATP synthase (cpATPase) and mitochondrial ATP synthase (mtATPase). Here, we show that loss of either Atp11 or Atp12 is lethal in Arabidopsis. While Atp12 is only localized in mitochondria, Atp11 is present both in chloroplasts and mitochondria. Yeast two-hybrid analyses showed that, as their homologs in yeast, Atp11 specifically interacts with the β subunit of the mtATPase and cpATPase, and Atp12 interacts with the α subunit of the mtATPase, implying that Atp11 and Atp12 fulfill a conserved task during assembly of ATP synthase. However, the binding sites for Atp11 in the β subunit of mtATPase and cpATPase are slightly different, suggesting that the mechanisms of action may have evolved in different ways. Although Atp11 interacts with cpATPase β subunit as the two assembly factors BFA3 and BFA1, they bind to different sites of the β subunit. These results indicate that Atp11 is involved in the assembly of both cpATPase and mtATPase but Atp12 is specifically required for the assembly of mtATPase in higher plants.